Pengaruh Pemberian Jus Buah Pir (Pyrus Communis) terhadap Pembersihan Stain Ekstrinsik pada Resin Komposit - Dendhana, Didiet S.; Wowor, Pemsi M.; Leman, Michael A. (e-GiGi, 2018)
Abstract: Tooth discoloration such as staining could possibly affect the condition of restorative treatment on the teeth caused by extrinsic and intrinsic factors. Bleaching could provide a solution to color changing problem of composite filling. Hydrogen peroxide (H2O2), the most common chemical agent to perform bleaching, is found naturally in pear fruit; therefore, it could be an alternative treatment to reduce stain of composite filling. This study was aimed to find out the stain removal effect of blended pear fruit on composite filling. This is a laboratory experimental study with a pre-post control group design. Total samples were 20 pieces of circular composites with 5 mm in diameter and 2 mm in thickness. The samples were submerged in coffee extract for 10 days to create visible extrinsic staining at their surfaces, and then the discoloration was measured with spectrophotometer. After that, the samples were divided into two groups with ten samples each: group A, submerged in coffee extract and group B submerged in blended pear juice for seven days. After the submerging procedure performed, all samples of group B were measured again with spectrophotometer. The results showed that in group B there was a significant effect on stain removal of composite resin (p <0.05). Conclusion: Blended pear fruit had stain removal effect in composite filling.Keywords: pear juice, extrinsic stain, composite resin.Â Abstrak: Perubahan warna gigi berupa stain dapat memengaruhi kondisi restorasi dalam rongga mulut yang disebabkan oleh faktor ekstrinsik dan intrinsik. Bleaching dapat dilakukan untuk menangani masalah perubahan warna resin komposit. Salah satu bahan bleaching yang sering digunakan di bidang kedokteran gigi ialah hidrogen peroksida (H2O2). Senyawa ini terkandung dalam buah pir yang dapat digunakan sebagai perawatan alternatif untuk mengurangi stain pada resin komposit. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian jus buah pir terhadap pembersihan stain ektrinsik pada resin komposit. Jenis penelitian ialah eksperimental laboratorium dengan pre and post control group design. Jumlah sampel penelitian ialah 20 resin komposit yang dibentuk dengan diameter 5 mm dan tebal 2 mm. Sampel direndam dalam larutan kopi selama 10 hari untuk melihat adanya stain ekstrinsik pada permukaan sampel resin komposit, kemudian dilakukan pengukuran perubahan warna dengan spektrofotometer. Setelah itu sampel dibagi atas dua kelompok masing-masih 10 buah sampel: kelompok A untuk perendaman dalam larutan kopi dan kelompok B untuk perendaman dalam jus buah pir selama tujuh hari kemudian sampel kelompok B dilakukan pengukuran kembali dengan spektrofotometer. Hasil penelitian menunjukkan terdapat pengaruh bermakna (p <0,05) terhadap pembersihan stain ekstrinsik pada resin komposit pada kelompok B. Simpulan: Pemberian jus buah pir dapat membersihkan stain ektrinsik pada resin kompositKata kunci: jus buah pir, stain ekstrinsik, resin komposit